Analisis teologis dan historis pemahaman tohonan sebagai jabatan dan ordinasi di Huria Kristen Batak Protestan - Binsar Jonathan Pakpahan (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
The Protestant Batak Christian Huria's understanding of the theology of office has received particular attention since the 2002 Church Order and Administration which was made after the Godang Reconciliation Synod. Church office, translated with the word tohonan are wrongly translated as tahbisan or ordination. The inconsistency influences direct or indirect the conclusion that the pastor??